PRACTISE - PhaRmAcist-led CogniTIve Services in Europe: preliminary results - Soares, Inês Branco (2018)
Communication presented at the 2nd International Congress of CiiEM: Translational Research and Innovation in Human and Health Sciences. 11-13 June 2017, Campus Egas Moniz, Caparica, Portugal